Solar Cell as Learning Multimedia to Improve Students’ Scientific Literacy on Science and Nanotechnology - Eliya wati; Yayan Sunarya; Ahmad Mudzakir (Universitas Pendidikan Indonesia, 2017)
This study aims to investigate solar cell as learning multimedia to improve students’ scientific literacy on science and nanotechnology. Specifically, it describes learning design, the characteristic of developed learning multimedia and the description of learning activities using solar cell as learning multimedia to improve students’ scientific literacy on science and nanotechnology. The method used in this research was Educational Research and Development that only consist of 3 stages. On the define stage, the research was conducted through literature review analysis, observation, and interview. On the design stage, the research was conducted through composing the instrument, developing solar cell as learning multimedia to improve students’ scientific literacy on science and nanotechnology and composing teaching learning design. On the develop stage, the research was conducted through teaching learning activities using solar cell as learning multimedia to improve students’ scientific literacy on science and nanotechnology. The research instruments were interview guideline, observation’s sheet, judgment’s sheet and questionnaire. Based on result and discussion, it can be concluded that learning design potentially improve students’ scientific literacy. It is relevant with learning material and in accordance with the competence aspect, attitude aspect, and STL learning model. The characteristics of learning multimedia containing science and nanotechnology on solar cell context are: can be used classically, not individually, student-centered oriented, presenting the learning material using concept approach and context oriented, presenting the superiority of photochemistry solar cell with nanotechnology, visualizing the redox reaction concept on solar cell, and presenting the concept through context description. The learning multimedia is used in all STL learning phases. It can be used by teacher to deliver the material in almost all phases of learning, while student use it when teacher give them instruction.